2011
DOI: 10.1093/qje/qjr033
|View full text |Cite
|
Sign up to set email alerts
|

Exports and Financial Shocks

Abstract: A striking feature of many financial crises is the collapse of exports relative to output. In the 2008 financial crisis, real world exports plunged 17 percent while GDP fell 5 percent. This paper examines whether the drying up of trade finance can help explain the large drops in exports relative to output. Our paper is the first to establish a causal link between the health of banks providing trade finance and growth in a firm's exports relative to its domestic sales. We overcome measurement and endogeneity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
426
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(484 citation statements)
references
References 29 publications
25
426
2
1
Order By: Relevance
“…Manova (2013) points out that more developed financial markets support industries with a higher dependence on external finance in exporting more. Amiti and Weinstein (2011) confirmed the link between access to external finance and international trade at the firm level. Kim, Lin and Suen (2010) examined the influence of international trade on financial development.…”
Section: Brief Literature Overviewmentioning
confidence: 57%
“…Manova (2013) points out that more developed financial markets support industries with a higher dependence on external finance in exporting more. Amiti and Weinstein (2011) confirmed the link between access to external finance and international trade at the firm level. Kim, Lin and Suen (2010) examined the influence of international trade on financial development.…”
Section: Brief Literature Overviewmentioning
confidence: 57%
“…A number of recent papers show the importance of financial linkages in explaining trade (Ahn et al, 2011;Amiti and Weinstein, 2011;Chor and Manova, 2012;Manova, 2008;Minetti and Zhu, 2011). For this reason, and to ensure that our main results are not driven by financial linkages, we include measures of financial linkages in our gravity regression.…”
Section: Empirical Gravity Model With Extensions and Export Riskmentioning
confidence: 99%
“…Further, they found that this effect was stronger in sectors more intensively requiring credit. Amiti and Weinstein (2010) demonstrate that when the health of banks which provide financing to Japanese exporters deteriorates, the value of exports by those firms also deteriorates, even relative to the value of their domestic sales. 3 Exports may be more credit or trade finance intensive than domestic sales.…”
Section: Introductionmentioning
confidence: 95%
“…As emphasized in Alessandria, Kaboski, and Midrigan (2010b), many of these explanations imply increases in the relative price of imported to domestically sourced goods, even within the same tradable sector. For example, Chor and Manova (2012), Amiti and Weinstein (2010), and a large subsequent literature emphasize the implications of tighter credit conditions for international trade values or volumes. 2 Chor and Manova (2012) find that during the recent trade collapse, U.S. imports declined by more from exporting countries which experienced greater increases in their borrowing costs (proxied for by the interbank rate).…”
Section: Introductionmentioning
confidence: 99%